2020
DOI: 10.1108/itse-01-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Student use of social media, academic performance, and creativity: the mediating role of intrinsic motivation

Abstract: Purpose The purpose of this paper is to investigate the relationships between students’ use of social media, their academic performance and creativity in the digital era. Design/methodology/approach This research used a survey strategy for collecting primary data required for this study from 334 students of undergraduate programs at Chinese universities who were sampled through a non-probability convenience approach. Findings The findings of the study reveal that students’ use of social media is positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 48 publications
4
26
0
3
Order By: Relevance
“…Intrinsic motivation is positively associated with student outcomes (Bempechat and Shernoff 2012;Saeed and Zyngier 2012). Specifically, research has found a positive association of students' intrinsic motivation with student engagement (Malik et al 2020;Yu et al 2019) and creativity (Du et al 2019;Soh 2017). We believe that student's intrinsic motivation is positively associated with social media utilisation by students, which, as a result, leads to student engagement & creativity.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Intrinsic motivation is positively associated with student outcomes (Bempechat and Shernoff 2012;Saeed and Zyngier 2012). Specifically, research has found a positive association of students' intrinsic motivation with student engagement (Malik et al 2020;Yu et al 2019) and creativity (Du et al 2019;Soh 2017). We believe that student's intrinsic motivation is positively associated with social media utilisation by students, which, as a result, leads to student engagement & creativity.…”
Section: Introductionmentioning
confidence: 82%
“…The tradition of social media in all walks of life has been increased rapidly in the recent years (Anser et al 2020;Rauniar et al 2014). Past researches revealed that social media is getting popular among students, and recent researchers have noted the considerable influence of social media utilisation in academia (Friesen and Lowe 2012;Greenhow and Lewin 2016;Malik et al 2020).…”
Section: Student Use Of Social Mediamentioning
confidence: 99%
See 3 more Smart Citations